Mechanical Properties and Microstructure of Forged Steel - Di Schino, Andrea; Sugimoto, Koh-ichi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on forged steels as an interesting material family, both from a scientific and commercial point of view, due to their many applications. Despite their diffusion as a consolidated material, many research fields are actively employing new applications. At the same time, innovations are arising from the manufacturing process of such materials, including the possibility to manufacture them from metal powders suitable for 3D printing. This reprint embraces the interdisciplinary work covering physical metallurgy and processing, reporting the experimental and theoretical progress concerning microstructural evolution during processing, and microstructure-properties relations.